2018
DOI: 10.1080/09273972.2017.1418394
|View full text |Cite
|
Sign up to set email alerts
|

Soft Contact Lenses to Optimize Vision in Adults with Idiopathic Infantile Nystagmus: A Pilot Parallel Randomized Controlled Trial

Abstract: CLs are well tolerated, with a low risk profile. Whilst our study was not powered to detect significant changes in BCVA and waveform parameters between treatment arms, we observed a trend towards an improvement in visual function at two weeks from baseline with CLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
5
0
3
Order By: Relevance
“…Theodorou et al [ 44 ] reported a pilot randomised control trial comparing fully corrective SCL with plano SCL in a group of 38 adult idiopaths. Despite the small effect size, there was an improvement in best corrected VA (BCVA) in both groups along with an improvement in some of the waveform parameters, in keeping with published data.…”
Section: Treatments and Ongoing Medical Carementioning
confidence: 99%
“…Theodorou et al [ 44 ] reported a pilot randomised control trial comparing fully corrective SCL with plano SCL in a group of 38 adult idiopaths. Despite the small effect size, there was an improvement in best corrected VA (BCVA) in both groups along with an improvement in some of the waveform parameters, in keeping with published data.…”
Section: Treatments and Ongoing Medical Carementioning
confidence: 99%
“…The self-administered VFQ-25 formed part of the baseline clinical data in an unmasked pilot parallel-randomised control trial assessing the use of contact lenses to optimise vision in adults with IINS 25 . All participants were required to complete the VFQ-25 questionnaire at the baseline study visit prior to randomisation.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies report improvements in visual acuity and eye movement and others show no changes or variable results [739][740][741][742][743]. These studies are mainly retrospective and small case series or reports.…”
Section: Nystagmusmentioning
confidence: 99%